AUTISTIC CHILDREN WITH INTELLECTUAL MUTISM: BARRIERS AND SOLUTIONS IN COMMUNICATION DEVELOPMENT (American Journal of Interdisciplinary Research and Development, 2025)
This article provides an in-depth analysis of intellectual mutism observed in children with Autism Spectrum Disorder (ASD), focusing on the psychological and neuropsychological barriers they face in the process of communication. The paper explores the underlying causes and mechanisms of these communication limitations, including the absence of verbal speech, lack of eye contact, and sensory processing difficulties, grounded in theoretical and scientific perspectives. Furthermore, the article presents advanced strategies and technologies aimed at facilitating the social integration and communicative competence of autistic children, such as visual communication tools, social stories, joint activities, sensory integration therapy, and the creation of inclusive environments. It also discusses national and international legal frameworks and highlights best practices that support the development of equitable educational opportunities for autistic children within a socially just environment.